Aneuploidia dos cromossomos 3, 7, 9 e 17 no câncer de próstata localizado tratado com cirurgia: análise e correlação prognóstica - Barros, Érika Aparecida Felix de (2014)
Prostate cancer (PCa) is the most common non-skin solid tumor in man in western countries. The prognosis is defined by the measurement of PSA, stage and Gleason score, however, none of these factors classics, even when combined, show good performance in prognosis definition, therefore molecular markers are being studied. Cytogenetic abnormalities, represented by chromosomal deletions and gains, are characteristic of oncogenesis and potentially can be used as a prognostic marker. Objectives: The study aimed to identify the cytogenetic alterations of aneuploidy in chromosomes 3 , 7 , 17 and 9p21 locus by FISH technique located in PCa underwent radical prostatectomy. As a secondary objective correlate the changes found with biochemical recurrence after surgical treatment and the classical prognostic factors of prostate adenocarcinoma. Methodology: For this case-control study 112 patients with clinically localized PCa who underwent radical prostatectomy were followed up postoperatively than ten years were analyzed. Samples of the primary tumor of each patient were available for tissue microarray matrix and cytogenetic changes were assessed by FISH technique. Results: Among the patients for the 9p21 locus, 6.4 % had lost one of the two alleles. In relation to the results obtained for chromosomes 3, 7 and 17 find deletion of one allele of 2.3, 1.2 and 1.8% of the cases respectively. No association between aneuploidy of these chromosomes with the Gleason score, pathological stage, serum PSA level or risk group . We observed that the loss of the 9p21 locus was associated with shorter time to recurrence (p 0.038 ). Conclusions: We found a low occurrence of aneuploidy detected by probes CEP 3 , 7 and 17 and LSI 9p in our series of tumors. We observed that the loss of the 9p21 locus was associated with worse prognosis in CaP located treated with surgery.